A Educação a Distância no Ensino Superior: perspectivas para a aprendizagem mediada pelas tecnologias digitais de informação e comunicação - TDICs - de Souza Viana, Neilane (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The aim of this paper is to discuss the use of mediated learning TDICs in higher education, with the object of focus system of the Open University of Brazil - UAB, which offers undergraduate courses in distance mode. For this it is necessary to briefly present some conceptual approaches of State, Education and Public Policy, as well as the social scene. Also worth mentioning some learning theories from Piaget and Vygotsky pervades due to the interactive process outlined in distance education through TDICs. You must also submit the operation of distance education, such modality used by the Open University of Brazil system.
Keywords: Distance Education; Digital Technologies; Public Policy